AN ASSESSMENT OF THE LEGAL STATUS OF ORGANIZER OF TRANSPORT SERVICE AND A RECOMMENDATION OF SUITABLE VARIANT (Perner's Contacts, 2011)
The paper deals with a problematic of assessment and recommendations of the  legal status of the organizer of transport service and integrated transport systems. It  summarizes the pros and cons of different legal forms, then recommend the most  suitable of the offer.
Keywords: organizer; transport service; integrated transport system